LOS ACUIFEROS COSTEROS DEL LITORAL ATLANTICO ENTRE PUNTA RASA Y PUNTA MEDANOS, PROVINCIA DE BUENOS AIRES, REPUBLICA ARGENTINA. - Arzac, R. G.; Vizcaino, A.; Alfonso, F. C.; Lorenzo, F.; Patrouilleau, R. (Águas Subterrâneas, 1990)
INDISPONÍVEL